2008
DOI: 10.1051/alr:2008024
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of water quality and stocking density on welfare and growth of rainbow trout (Oncorhynchus mykiss)

Abstract: An 84-day experiment assessed the combined effects of two fresh water quality levels (H: 1.71 ± 0.15 mg O 2 l −1 and 0.28 ± 0.01 mg l −1 total ammonia nitrogen (T-AN), L: 5.15 ± 0.07 mg O 2 l −1 and 0.54 ± 0.01 mg T-AN l −1 ) and 3 stabilized stocking densities: 24.8 ± 0.2, 74.2 ± 0.5 and 120.0 ± 0.9 kg m −3 ) on rainbow trout. Fish were fed using demand feeders with rewards proportional to stocking density. Mass increase was significantly affected by water quality and stocking density, being highest in H wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 43 publications
(57 reference statements)
5
41
0
Order By: Relevance
“…Sudden changes in the fish stocking density, growth rate, feeding rate or water volume can elicit rapid changes in water quality; hence, regular measurement of those critical water quality parameters is essential. The deterioration of water quality parameters affects fish physiology, growth rate, and feed efficiency, leading to pathological changes and even mortality under extreme conditions [4,5]. In terms of aquaponic systems and considering the fish welfare issues, carrying capacity is of major concern for maintaining the balance between plant and fish requirements in a co-culture medium.…”
Section: Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden changes in the fish stocking density, growth rate, feeding rate or water volume can elicit rapid changes in water quality; hence, regular measurement of those critical water quality parameters is essential. The deterioration of water quality parameters affects fish physiology, growth rate, and feed efficiency, leading to pathological changes and even mortality under extreme conditions [4,5]. In terms of aquaponic systems and considering the fish welfare issues, carrying capacity is of major concern for maintaining the balance between plant and fish requirements in a co-culture medium.…”
Section: Water Qualitymentioning
confidence: 99%
“…Carrying capacity expresses the maximum biomass of fish in the system with acceptable water quality limits. The carrying capacity of a given amount of water is determined by the oxygen consumption rate of the fish and their responses to ammonia, CO 2 and other potentially toxic metabolic wastes that are produced [5]. Stress involves a series of physiological and behavioural reactions that help fish resist death or adapt to changing conditions.…”
Section: Water Qualitymentioning
confidence: 99%
“…This index was greater in all fish subjected to exercise, independently of the stocking density, probably because sedentary fish under high densities spend more energy to cope with crowding stress. The combined effects of water quality and high stocking densities also reduced the values of the K of rainbow trout due to low water quality and feeding conditions, causing alterations to fish welfare (Person-Le Ruyet et al, 2008). In the present study, the sharing of the food pellets and the water quality were improved, and the aggressive behavior was reduced, sparing energy for the anabolic processes.…”
Section: Resultsmentioning
confidence: 51%
“…The regression analysis showed that SD was not a significant predictor in every examined fin model (Table 4 -Table 10). Fin damage is historically linked to SD (3) and the main approach was that higher densities will increase the level of fin damage (26)(27)(28)(29)(30)(31). In our study, SD was the only factor that did not have an effect on the level of fin damage.…”
Section: Discussionmentioning
confidence: 99%
“…Routine handling affects the level of fin damage as fish come into physical contact with surfaces (nets, grading equipment, vaccination tables) and with other fish during crowding within the rearing units prior to vaccination, grading and processing (3,30,38). In our study, GR received the strongest weight in the model only for the dorsal fin, but higher levels of GR predicted the damage of the dorsal, caudal, anal and left pelvic fin.…”
Section: Discussionmentioning
confidence: 99%